Health literacy and school-based health education - Marks, Ray (Emerald Group Publishing Limited, 2012)
Health literacy plays a critical role in the understanding and application of health related information. This work describes the concept of health literacy and the development of health literacy skills among children and young people, whilst also discussing the economics of health illiteracy.